Clinical profile, risk factors and outcomes of ectopic pregnancy in a tertiary care hospital - Sharma, Suchi; Das, Jayita; Sharma, Reena (International Journal of Research in Medical Sciences, 2025)
Background: Extrauterine or ectopic pregnancy occurs when the fertilized ovum becomes implanted in tissue other than the endometrium. Aim of this study is to find the incidence, clinical presentation, risk factors, management of ectopic pregnancy. Methods: It was an observational study done in the department of obstetrics and gynaecology, Shri Lal Bahadur Shastri medical college Mandi, Himachal Pradesh for period of one year from 1st January 2024 to 31st December 2024. Results: A total 3628 women delivered in the tertiary care hospital during the study period of one year. The incidence of ectopic pregnancy was 1.87%. The most common age group was 20-30 years. Incidence of ectopic pregnancy was more in multipara (73.53%). Most common clinical presentation was amenorrhoea in 95.58% followed by abdominal pain in 80.88% patients. The failed tubal ligation was the risk factor in 14.74% patients. Unilateral salpingectomy was done in 45.58%, methotrexate treatment in 50%, expectant treatment in 2.94% and laparotomy for one caesarean scar ectopic pregnancy. Anaemia was observed in75.6% patients, blood transfusion in 55.2% and ICU admissions were 5.8%. Conclusions: Early recognition of ectopic pregnancy is the key to diagnosis and management. It is important to maintain high degree of suspicion of ectopic pregnancy with pregnancies of unknown location.